PROFESSIONAL SOCIALISATION IN NURSING: CONCEPT ANALYSIS - Kanyamura, Dorothy; Longwe, Rachael; Haruzivishe, Clara; Kasu, Christine; Gwariro, Simba; Dzimiri, Tafara; Ncube, Francis; Musvipa, Mary; Ncube, Belitha; Maxwell, Mhlanga; Ndaimani, Augustine (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2016)
The goal of this concept paper is to define, describe and clarify the concept of professionalsocialization in nursing. In this paper attributes, antecedents, consequences and empiricalreferents of professional socialization were also identified. This paper was guided by Walker &Avant model, 2005 to clarify the concept of professional socialisation in nursing. A literaturereview was done by performing a search on scientific data base, PubMed and Google Scholar.Key terms that were used were: socialization, nursing and professionalization. Twenty onearticles were reviewed and nine articles were selected for this concept analysis.Professionalization is a process with the four identified attributes which are interaction, learning,adaptation and development. The antecedents identified were competent role model, professionof adequate field experience and comprehensive educational programme. Consequences werealso identified. These findings add to the body of knowledge of professional socialization in nursing. Some of the empirical referents which are critical in tool development for professionalsocialization in nursing include high levels of student engagement, positive student responses tonursing, role modeling and positive personal professional development.